Magnetically guidable single TiO2 nanotube photocatalyst: Structure and photocatalytic properties. Issue 4 (15th February 2023) - Sepúlveda, Marcela; Saldan, Ivan; Mahnaz, Alijani; Cicmancova, Veronika; Michalicka, Jan; Hromadko, Ludek; Bulánek, Roman; Sopha, Hanna; Macak, Jan M.
Abstract: The influence of annealing temperature, the crystallinity, textural properties of magnetically guidable anodic TiO2 nanotubes in form of single tube powders on the photocatalytic decomposition of model organic dye is investigated for the first time. The powders were prepared from self-organized anodic TiO2 nanotube layers (grown on Ti) by etching in piranha solution, detaching them from the Ti substrate, and annealing in a wide range of temperatures (400–900 °C). The nanotubular shape was preserved up to 800 °C. Powders annealed up to 800 °C did not contain any detectable rutile phase, which is unique among other TiO2 nanomaterials at this temperature. Part of the obtained TiO2 ST-NT powders was decorated with Fe3 O4 nanoparticles using an oleic acid-based synthesis. The TiO2 ST-NT and TiO2 ST-NT@Fe3 O4 NPs powders were characterized in terms of morphology, crystallinity, and specific surface area. Finally, all materials were exploited for the photocatalytic decomposition of a model dye. The best photocatalytic performance of TiO2 ST-NT and TiO2 ST-NT@Fe3 O4 NPs powders were obtained at annealing temperatures of 600 and 700 °C, respectively. The synergy resulting from annealing, crystallite size, and specific surface area enhances the photocatalytic activity of TiO2 ST-NT and TiO2 ST-NT@Fe3 O4 NPs powders under UV light. This approach goes beyond the classical Kasuga alkaline hydrothermal approach, enabling the preparation of large quantity of TiO2 nanotubes without any impurities (such as e.g. Na or Ca content resulting from the Kasuga approach).